A COMPARISON ON PHYTOCHEMICAL AND PHYSICOCHEMICAL EVALUATION OF STEM PART OF PLANTS KALANCHOE PINNATUM AND KALANCHOE CRENATA (ADREWS) HAW - Bhatti, Manisha; Puri, Ritika (Journal of Biomedical and Pharmaceutical Research, 2018)
Kalanchoe pinnata (Lam.) Pers. and K. crenata (Andrews) Haw. of family Crassulaceae, are popularly used in the treatment of many diseases. [1] Both species are often misidentified as the other, because of their similar popular uses and names, and the similar external morphology of the leaves. [1] They show close proximity in usage, habitat, preparation and identification. The external morphological features of Kalanchoe crenata resemble that of Kalanchoe pinnatum. Ethnobotanically, most often they are prepared and administered the same way.[2] The plant is rich in both macro and micro elements, vitamins, calcium, phosphorus, ascorbic acid, inulin [3] and other compounds like saponin, flavonoids, anthraquinones, xanthones, bryophyllin A and B.[4] Alkaloids and saponins are present in the aqueous and alcoholic extracts of plant parts. [6] The green callus of the plant contains malic acid, quinones and tocopherol. [7] The present research includes phytochemical and physicochemical evaluation of stems of Kalanchoe pinnatum & Kalanchoe crenata. KEYWORDS: Kalanchoe pinnatum, Kalanchoe crenata, phytochemical evaluation, physicochemical evaluation